Anodization as a promising surface treatment for drug delivery implants and a non-cytotoxic process for surface alteration: a pilot study. - Kunrath, M. F.; Penha, N.; Ng, J. C (Journal of Osseointegration, 2020)
Aim Surface treatments use industrial processes in which surface contamination can occur. In this context, this study aimed to demonstrate a surface treatment process, from laboratory samples and clinical implants, named anodizing, analyze their tendencies to surface contamination as well as their properties. Materials and Methods Laboratorial samples of pure titanium were anodized. Investigated by scanning microscopy (SEM), dispersive energy spectroscopy (EDS) and wettability tests. Four implant systems available in the current market were chosen by different surface treatments (anodizing, double acid etching and particle blasting) and investigated by SEM/EDS. Results Laboratory samples showed a nanomorphology surface, free of contaminants and good liquid/surface interaction. The implant system with anodization treatment did not present elements outside the standards. However, the implants treated with acid attack and blasting were found different chemical elements like aluminum and magnesium. Conclusions Anodizing proved to be a contaminant-free surface treatment both in the laboratory and clinical implants. In addition, its promising property of owning TiO2 nanotubes suggests an inherent evolution to biomedical implants for drug delivery systems other than all surface treatments developed to date.